The Toponymic Etymology of the Word Titicaca - Quispe Ilasaca, Raul Valentin (2022)
There are several arbitrary translations of the word Titicaca, which is why its search generated confusion due to its departure from Quechua or Aymara. The objective of this research is to determine and explain linguistically the meaning of the word Titicaca. Methodologically, the study is of an explanatory nature, which is based on the review of linguistic and ethnohistorical sources (chronicles), which allow comparison with ethnographic sources based on studies and toponym decoding procedures developed by Cerrón-Palomino (2013, 2020, 2021). The article concludes that the word Titicaca has a Puquine and Quechua filiation, as contemporary research shows; therefore, it is affirmed that titiqaqa means 'rock of the sun'. Thus, the previous postulates about its meaning are discarded. Likewise, according to archaeological and ethnohistorical data, the importance of the island of the sun influenced the puquinas lake to acquire the name of the great divinity that exists there.